Evaluation of the Implementation Integrated Biological System Industrial Wastewater Treatment Plant: Pollutant Removal, Operational Maintenance, Estimation of Carbon Emission - Setianingsih, Nanik Indah; Farida Crisnaningtyas; Agus Purwanto; Ikha Rasti Julia Sari (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2022)
The development of WWTP in business activities needs to pay attention to getting appropriate WWTP that is more valuable to support sustainable development. This study aims to evaluate two systems of integrated biological WWTP; anaerobic-wetland, and anaerobic-aerobic-wetland, including the effectiveness of pollutant removal, operational and maintenance, and estimation of carbon emissions. The performance of pollutant removal was evaluated by analyzing inlet and outlet samples of WWTP. An operational and maintenance evaluation was carried out by studying the WWTP operating system and maintenance procedures supported by a literature review. Carbon emission estimation was carried out using a formula referring to the IPCC Guidelines (2006). Organic matter removal of anaerobic-aerobic-wetland WWTP in the form of BOD₅ and COD are 92.12% and 91.72%, respectively, higher than anaerobic-wetland WWTP are 88.69% of BOD₅ and 77.62% of COD. Anaerobic-aerobic-wetland WWTP needs more maintenance and operation than anaerobic-wetland WWTP. The highest carbon emission of both WWTP is 41530.91 kgCO₂ eq/year of anaerobic-wetland WWTP from the organic matter removal process and 46485.15 kgCO₂ eq/year of anaerobic-aerobic-wetland WWTP. Electrical energy consumption emits in anaerobic-aerobic-wetland WWTP is 22338 kgCO₂ eq/year higher than anaerobic-wetland WWTP at 4299.70 kgCO₂ eq/year. Total carbon emissions of anaerobic-wetland WWTP is 47404.58 kgCO₂ eq/year and anaerobic-aerobic-wetland WWTP is 68900.23 kgCO₂ eq/year.